Persicaria tuminensis (Polygonaceae, Persicarieae), a new species of the section Echinocaulon from the wetland flora of the Tumen River valley - Chubar, Elena A. (Phytotaxa, 2025)
Persicaria tuminensis is here described as a new species belonging to the sect. Echinocaulon (Polygonaceae) from the lower Tumen River valley (Russian Far East). A description, original images, and a morphological comparison with the similar East Asian and American species are provided. P. tuminensis differs from the other species of this section by the entire, linear-lanceolate leaves, attenuate to the apex and the base, basally truncate, subrounded or barely subhastate; the ocreae, being are initially tubular but open in maturity, often lacerate, with a short-ciliated truncated upper margin; and the bracts subtending flower fascicles widely rhomboid to subrounded and funnelform, with a densely bristly outer surface and long-ciliated oblique upper margin. In addition to macro-morphology, the new species has differences in the achene surface pattern.